2010
DOI: 10.1007/s11999-010-1412-7
|View full text |Cite
|
Sign up to set email alerts
|

Bioabsorbable Tricalcium Phosphate Bone Cement Strengthens Fixation of Suture Anchors

Abstract: Background Failure of suture anchor fixation in rotator cuff repair can occur at different interfaces. Prior studies show fixation at the bone-anchor interface can be augmented using polymethylmethacrylate (PMMA) cement, and screw fixation into bone can be strengthened using bioabsorbable tricalcium phosphate cement. Questions/purposes We wished to determine whether augmentation of suture anchor fixation using bioabsorbable tricalcium phosphate cement would increase pullout strength of suture anchors from bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 22 publications
2
13
0
2
Order By: Relevance
“…Regarding bio-absorbable cement Oshtory et al have demonstrated that augmentation with calcium phosphate effects an increase by 29 % [9]. In the present study, the failure load could be enhanced by 66.8 % by the augmentation with fiber-reinforced calcium phosphate.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Regarding bio-absorbable cement Oshtory et al have demonstrated that augmentation with calcium phosphate effects an increase by 29 % [9]. In the present study, the failure load could be enhanced by 66.8 % by the augmentation with fiber-reinforced calcium phosphate.…”
Section: Discussionsupporting
confidence: 54%
“…Regarding RC reconstruction the potential impairment of the footprint area has to be avoided. Oshtory et al could already show that augmentation of anchors with calcium phosphate cement also leads to a significant increase in failure load, but the increase was found to be much lower than the increase which occurred with PMMA [9]. In the recent past, efforts have been made to enhance the characteristics of biocompatible calcium phosphate cements by reinforcing them with fibers (e.g., polylactide/glycolide copolymer fibers).…”
Section: Introductionmentioning
confidence: 99%
“…Ninety-five percent confidence intervals (CIs) on these estimators indicated fair to near-perfect agreement, with comparable agreement between raters and modalities. The agreements (22). Trabecular structure is not well visualized, owing to the spatial resolution relative to not available with standard MR pulse sequences.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of a self-setting nature, biocompatibility, lack of any by-products and a great potential for replacement by bones make calcium orthophosphate cements, concretes, pastes and putties very promising materials for clinical and medical applications. In addition, they can easily be used by bone remodeling cells for reconstruction of damaged parts of bones [102,103,226,392,[470][471][472]. The ability to be molded in place also is a very important property because these formulations can easily be delivered into the desired place and can be fitted perfectly with bone defects [103].…”
Section: Clinical and Medical Applicationsmentioning
confidence: 99%